Reversing cardiac hypertrophy and heart failure using a cardiac targeting peptide linked to miRNA106a - Ming Lu; Siqi Cai; Kyle Korolowicz; Claire Deng; Kaan Taskintuna; Gerard Ahern; Raymond B. Yurko; Kazi R. Islam; Bryn Schoonover; Jack B. Lopuszynski; Hongkun Wang; Maliha Zahid; et al. (Clinical and Translational Medicine)
Abstract Background One in five adults aged 40 will develop heart failure (HF) during their lifetime. Risk factors (e.g., hypertension, diabetes mellitus, coronary artery disease, etc.) lead to structural and functional changes in cardiomyocytes, resulting in HF. At the cellular level, these changes consist of mis/over‐expression of genes that regulate cardiac identity (e.g., CamK2δ, PKC, Stat3, etc.). The current paradigm for treating HF is pharmacological or device‐based intervention; however, with few exceptions, the condition worsens with time. We are proposing to implement a change in HF treatment, shifting from a drug‐centric system to a cardiac target‐specific molecular approach that would reverse hypertrophy and adverse remodelling of affected cardiomyocytes. Methods A cardiomyocyte targeting peptide (CTP) was reversibly linked to miRNA106a for delivery to a mouse model of HF. Reversal of morphological, signalling, and physiological HF parameters was measured. Additionally, CTP‐miRNA106a was introduced into a human cardiomyocyte cell line to identify mechanism(s) at play for reversing HF characteristics (e.g., hypertrophy). Results Bio‐distribution studies showed that intravenously injected CTP‐miRNA106 delivered its cargo specifically to the heart within 30 min, followed by clearance of CTP from the heart to the kidneys, and to a lesser extent, the liver by 35 h with persistence of miRNA106a in cardiomyocytes until day 7 (the latest tested time‐point). CTP‐miRNA106a reversed angiotensin2/isoproterenol‐induced hypertrophy in 90% of the treated mice. We also identified two potential HF intracellular signalling pathways/mechanisms (PLCβ1/PKC/IP3 and NF‐κB) targeted by CTP‐miRNA106a that could benefit many pathophysiologies underlying HF, including inflammation. Conclusions CTP‐miRNA106a, a first‐of‐a‐kind cardiac‐specific drug, downregulates genes involved in cardiac hypertrophy and inflammation through the PLCβ1 and CamKIIδ kinase pathways. CTP delivery of miRNA106a cargo is specific to cardiomyocytes both in vitro and in vivo, and once delivered, many HF parameters, including hypertrophy, are reversed. Key points Cardiac Targeting Peptide (CTP) delivers, specifically to the heart, reversibly linked miRNA106a. MiRNA106a targets genes in various pathways known to cause heart failure when they are over/hyper activated returning their expression to normal levels. In vivo analyses using a mouse heart failure model resulted in reversal of heart failure parameters in 19/20 mice.